Entrepreneurship vs. Freelancing: What’s the Difference? - Huđek, Ivona; Tominc, Polona; Širec, Karin (Naše gospodarstvo/Our economy, 2022)
The development of Internet technology (IT) at the end of the 20th century and its integration into the business sector has led to the emergence of digital labour platforms that provoke a reorganization of work arrangements by matching the demand and supply of goods and services, known as the “gig economy”. The “gig economy” stands for economic activities or work arrangements related to the performance of very short-term tasks facilitated by digital platforms and can include freelance work, temporary work, work on-demand and contract work. Our paper focuses on the new, growing workforce of freelancers. Freelancers belong to the self-employed category of entrepreneurial activity who do not employ workers, who pay their own taxes, work on projects, work for several clients, and work remotely, usually from home. According to various sources and findings, they are also referred to as entrepreneurs, solopreneurs, digital micro-entrepreneurs, hybrids of employees and entrepreneurs, enablers of entrepreneurship, potential entrepreneurs, etc. The purpose of this paper is to examine the relationship between freelancers and entrepreneurs. The paper will use a literature-review approach to highlight the similarities and main differences between freelancers and entrepreneurs and to find an answer to the question whether freelancers can be considered entrepreneurs or not. In addition, the paper provides insights into freelance work and highlights the benefits and challenges that freelancers face in the labour market.